Addressing context to understand physical activity among Muslim university students: the role of gender, family, and culture - Ghadir Fakhri Aljayyousi; Maher Abu Munshar; Farid Al-Salim; El Rayah Osman (BMC, 2019)
Abstract Background Physical inactivity is a crucial risk factor for the development of chronic health issues, which have a high incidence among Arabs living in the Gulf Cooperation Council (GCC) countries. The Qatar Stepwise Survey 2012 reported that approximately 44% of young adults 18-44 years of age had insufficient levels of physical activity. Family is a powerful source of information and socialization for adolescents and has a strong influence on their attitudes, decision-making, and behaviors. Methods The purpose of this study is to understand how university students' physical activity can be influenced by sociocultural factors, particularly family health values and Muslim Arab culture. Using the criterion sampling strategy, 20 undergraduate Muslim students (Female students =10, Male students = 10) aged from 18 to 23 years who were Qatari or born and also raised in Qatar were recruited and interviewed. Participants were asked if they consider themselves active or not, about their perception of family health values regarding physical activity and the factors shaping these values, and the influence of family values on their physical activity behavior. The interviews were transcribed verbatim, coded, and analyzed following inductive analysis. Results The majority of the participants were influenced by their family health values, which were shaped by Qatari culture and the culture of origin for non-Qatari and were implicitly shaped by Islam. Participants reported that their role models of physical activity were males (fathers and male siblings), a health condition will motivate their families to be physically active, and families give priority to work and academic achievement over physical activity. A few participants showed that there was explicit influence of Islam on their physical activity, because culture's influence was veiling religion's. Culture was seen as a facilitator for physical activity from the males' perspectives, which was not the case for female participants who reported the negative influence of culture on their physical activity because of the limited choices available for them. Non-Qatari students revealed that their culture of origin (such as Syria, Palestine, Egypt, Somalia, Bangladesh, Sudan, Pakistan and India) was the dominant factor in shaping their family health values. Conclusions The findings address gaps in the literature about families' health values regarding physical activity in Qatar, the influence of the different ecologies surrounding these values, and the physical activity behaviors of university students. Knowledge about these factors can aid in the development of family-based interventions designed to motivate adolescents to be physically active, which should be religion- and culture-tailored.